Not guilty: are the acquitted innocent? - Givelber, Daniel (New York Univ. Press, 2012)
Introduction : invisible innocence -- Judge and jury decisions to acquit : what we know from social research -- Screening for innocence -- Understanding why judges and juries disagree about criminal case outcomes : are jury verdicts an expression of sentiment? -- The defense case -- The impact of race on judge and jury decision making -- Conslusion